Gut microbe-generated metabolite trimethylamine-N-oxide as cardiovascular risk biomarker: a systematic review and dose-response meta-analysis - Schiattarella, Gabriele Giacomo; Sannino, Anna; Toscano, Evelina; Giugliano, Giuseppe; Gargiulo, Giuseppe; Franzone, Anna; Trimarco, Bruno; Esposito, Giovanni; Perrino, Cinzia (European heart journal, 2017)
Gut microbiota-derived metabolite trimethylamine-N-oxide (TMAO) is emerging as a new potentially important cause of increased cardiovascular risk. The purpose of this meta-analysis was to systematically estimate and quantify the association between TMAO plasma levels, mortality, and major adverse cardio and cerebrovascular events (MACCE). MEDLINE, ISI Web of Science, and SCOPUS databases were searched for ad hoc studies published up to April 2017. Associations between TMAO plasma levels, all-cause mortality (primary outcome) and MACCE (secondary outcome) were systematically addressed. A total of 17 clinical studies were included in the analytic synthesis, enrolling 26 167 subjects. The mean follow-up in our study population was 4.3 ± 1.5 years. High TMAO plasma levels were associated with increased incidence of all-cause mortality [14 studies for 16 cohorts enrolling 15 662 subjects, hazard ratio (HR): 1.91; 95% confidence interval (CI): 1.40-2.61, P < 0.0001, I2 = 94%] and MACCE (5 studies for 6 cohorts enrolling 13 944 subjects, HR: 1.67, 95% CI: 1.33-2.11, P < 0.00001, I2 = 46%,). Dose-response meta-analysis revealed that the relative risk (RR) for all-cause mortality increased by 7.6% per each 10 μmol/L increment of TMAO [summary RR: 1.07, 95% CI (1.04-1.11), P < 0.0001; based on seven studies]. Association of TMAO and mortality persisted in all examined subgroups and across all subject populations. This is the first systematic review and meta-analysis demonstrating the positive dose-dependent association between TMAO plasma levels and increased cardiovascular risk and mortality.